Penanaman Nilai Tradisi Kepesantrenan Dalam Membendung Radikalisme Agama: Studi Pondok Pesantren An Nahdlah Makassar - Khairunnisa, Khairunnisa (Al-Riwayah : Jurnal Kependidikan, 2020)
Kitab Kuning tradition conserved by boarding schools recently is identical as a place of terrorism, and of course the stigma is a very erroneous reading. Boarding School is viewed with suspicion, stigmatic, so the boarding school institution as the "last fort" of moral guardians face delegitimation. An Nahdlah boarding school in Makassar as an educational institution teaching Kitab Kuning without teaching violence. It is seen from the teaching methods and the curriculum taught. Application of the religious curriculum at all does not lead to the issue of radicalism but focuses on aspects of faith, morals, interpretation, fiqhi, muamalat and tasawuf, so it is avoided from the radical understanding and builds religious understanding according to the Islamic teaching that teaches peace